2013
DOI: 10.5430/jst.v3n2p35
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1alpha in lung carcinoma: Histopathological evidence of hypoxia targets in patient biopsies

Abstract: Background: Hypoxia inducible factor 1alpha (HIF-1alpha) plays a major role in the response of tumors to hypoxia, and contributes to tumor aggressiveness, invasiveness and resistance to radiotherapy and chemotherapy. Targeting HIF-1alpha is an attractive strategy, with the potential for disrupting multiple pathways crucial for tumor growth. Thus, the evaluation of HIF-1alpha in patient biopsies could be useful in personalized cancer treatment. Methodology:The current literature on HIF-1alpha immunohistochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
(93 reference statements)
0
2
0
1
Order By: Relevance
“…The hypoxia-inducible factor-1 (HIF-1) is an oxygen-sensitive transcriptional activator and is causally involved in NSCLC [ 77 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…The hypoxia-inducible factor-1 (HIF-1) is an oxygen-sensitive transcriptional activator and is causally involved in NSCLC [ 77 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hypoxia promotes metastasis in CRC through the activation of the hypoxia inducible transcription factors (HIFs), HIF‐1α, and HIF‐2α, which regulate genes associated with tumor growth, invasion, angiogenesis, glucose metabolism, EMT, and treatment resistance (Ioannou et al, 2015; X. Lu & Kang, 2010). Several studies suggested curcumin and its analogs as reducers of HIF activity in several human tumor cell lines.…”
Section: Role Of Curcumin In Crcmentioning
confidence: 99%
“…В литературе имеются данные об увеличенной экспрессии HIF-1α, ГК и CD44v6 в клетках НМКРЛ и их ассоциации с плохим прогнозом заболевания [9][10][11]. Рост уровня биомолекул в опухолевой ткани закономерно сопровождается выходом их из опухолевых клеток в кровь.…”
unclassified